2009
DOI: 10.1080/09639280902719390
|View full text |Cite
|
Sign up to set email alerts
|

Professional Skills and Capabilities of Accounting Graduates: The New Zealand Expectation Gap?

Abstract: Much has been written about teaching and learning deficiencies in accounting education. Universities have grappled with the challenge and developed a number of strategies to address the concerns raised. Many of the recommended strategies for addressing these deficiencies have included a focus on the development of professional capabilities and skills. This paper reports on a study which has identified the capabilities which are considered to be the most important for successful practice in accountancy during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
84
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(105 citation statements)
references
References 27 publications
13
84
0
8
Order By: Relevance
“…This is consistent with other research examining case-studies as a teaching method in accounting education (e.g. Dennis, 2003;Green & Calderon 2005;Jackling & De Lange, 2009;Wells et al, 2009). …”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…This is consistent with other research examining case-studies as a teaching method in accounting education (e.g. Dennis, 2003;Green & Calderon 2005;Jackling & De Lange, 2009;Wells et al, 2009). …”
Section: Introductionsupporting
confidence: 81%
“…Consequently, there is wide coverage in the literature of the importance of bringing real-life appreciation and application into accounting teaching (Boyce et al, 2001;Drake, 2011;Healy & McCutcheon, 2010;Montaño et al, 2001). Beyond this, the specific involvement of practitioners in academic courses highlights the practical relevance of learning and helps to more fully prepare accounting students for employment (Bonk & Smith, 1998;Cranmer, 2006;Howieson, 2003;Wells et al, 2009). Indeed, within the accounting education literature, there is an increasing recognition of the potential for greater collaboration between academic institutions and accounting practitioners to help in more fully integrating theory and accounting practice in an academic environment (Donovan, 2005;Wilson et al 2008;Wilson, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Even more, it was often found that teachers do not consider generic skills as important for accounting practice (Hunt et al, 2004, Wells et al, 2009. It follows that emphasis placed by universities on technical skills is more pronounced.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Traditionally considered as a score-keeper, a bean counter and a corporate cop (Siegel, 2000), the accountant must be now regarded as a professional with a sense of leadership, able to manage a team and to exercise a rigorous and transparent judgement in several situations (Williams, 1994;Bescos, 2002;Howieson, 2003;Jones and Abraham, 2009). As a result, employers / recruiters are seeking a diverse range of skills and attributes in new accounting graduates (Wells et al, 2009;Kavanagh and Drenan, 2008). In this context, Birrell (2006) suggests that the managerial needs to take quick action and to maintain the competitive position, pushed employers to model a new accounting graduate profile with a large range of technical and generic skills.…”
Section: Introductionmentioning
confidence: 99%
“…The term generic skills has been widely used in the accounting education literature (Albrecht and Sack (2000); Kavanagh and Drennan (2008); Lin (2008); Jackling and De Lange (2009) ;Wells, Gerbic, Kranenburg, and Bygrave (2009); Bui and Porter(2010)). Abayadeera and Watty (2016:p149) define generic skills as those capabilities required by graduate accountants for employability and career advancement.…”
Section: Introductionmentioning
confidence: 99%